Electrochemical preparation and characterization of a gold nanoparticles graphite electrode: Application to myricetin antioxidant analysis - Ng, K.L.; Lee, S.M.; Khor, S.M.; Tan, G.H. (2015)
Graphite material is abundantly available from recyclable sources. It possesses a good electrical conductance property, which makes it an attractive material as a working electrode. However, due to a high activation overpotential it has limited applications as compared to other solid metal electrodes. In this present work, we obtained a graphite rod from a used battery, and carried out electrochemical improvements by electro-deposition with gold nanoparticles (AuNPs). The heterogeneous electron transfer rate and electron transfer resistance of the fabricated electrode were improved. The electrode overpotential has shown improvement by 50 mV, and the effective surface area has increased by 2 fold. To determine the practicability of the AuNPs/graphite electrode, we used the electrode in the analysis of myricetin. A square- wave voltammetry was used in the analysis, and the detection response increased by 2.5 fold, which suggested an improvement in the electrode sensitivity.